(3JfbjM GdCfXGQ hJdbjM GdCacGQ HeYGfi ebOeI GdCKeGQs - (3YHO Gddg Hf TQa GdOjfs ((3fGUQ GdMb Hf TeS GdOjf s)
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai , QHfG CJee dfG fhQfG hGZaQ dfG , Efc Ydi cd TF bOjQ gPg ebOeI dHjGf s
(3BNQgG (B:s
(3aef CQGO fbdg Ydi GdbQGAg aYd hfQLh ef Gddg GdJHdjZ dPdc agh MSHi hfYe Gdhcjd Je Pdc s
(3GdfSNI HgG MhGTs
(3HgG aQGZ ef GdOGNd dYdg ef GdfGSNs
(3Ydi MhGTjgG JYdjbGJ hebGHdGJs
(3hcJHJ HdYV GdYfhGfGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdESdGejs